Social and cultural shifts on art worker community towards current globalization - Merta, I Nengah (International research journal of management, IT and social sciences, 2019)
The purpose of this study is to find out and describe the social and cultural shifts of the art worker community due to the current of globalization in the Junjungan village of Ubud, Bali. Advances in technology and information are very fast causing all components of life to experience a shift both social and cultural Junjungan Ubud people began to experience a very drastic shift along with changes in human civilization at this time. This study uses a qualitative descriptive method, using proportional sampling techniques consisting of arts workers and the community who work in the tourism sector in the village of Junjungan Ubud, Bali. The social and cultural shift of the people of Junjungan Ubud Village in Bali is inseparable from the embryo of globalization that is felt in all sectors of people's lives. Globalization is the spread of certain values ??and cultures throughout the world. Globalization which makes the world smaller is seen in terms of human interaction due to the development of technological science, art and information holistically. Things that need to be improved gradually and consistently in the form of human resource management through competitive vocational education with other ASEAN friendly countries.